PENGEMBANGAN MEDIA AJAR BERBASIS ARTIFICIAL INTELLIGENCE PADA MATA KULIAH EVALUASI PEMBELAJARAN MATEMATIKA - Sari, Raras Kartika; Avianty, Donna (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This research is a development research (R&D). This study aims to develop learning media based on Artificial Intelligence (AI) in mathematics learning evaluation courses. The research was developed using the ADDIE model (analysis, design, development, implementation and evaluation). The media was developed by utilizing several AI tools, namely ChatGPT, Fliki, Toonme and D-ID. Experts provide an assessment of AI-based media with an average rating of Good. Media gets 78% Good in terms of appearance, 85% in a very good category in terms of use, and 80% in a good category in terms of presentation of material. Based on the assessment of material experts, the products that have been developed get 79% in the good category in terms of the suitability of the teaching materials and the assessment of the coherence of the material is 80% in the good category. Based on the assessment of linguists, the developed product received an 82% rating in the very good category in terms of the language used. A score of 78% is in a good category in terms of the pronunciation of the language in audio and a score of 79% is in a good category in language selection. Based on the results of the validation and assessment of experts, small group trials, large group trials and then revisions to the initial media products developed, the Artificial Intelligence-based learning media for mathematics learning evaluation courses is declared feasible to be used and exploited in the field.